2016
DOI: 10.1097/icu.0000000000000296
|View full text |Cite
|
Sign up to set email alerts
|

A review of the current practice in diagnosis and management of visual complaints associated with concussion and postconcussion syndrome

Abstract: Currently, there is not a single testing method that can universally identify all individuals with concussion. Current management of concussion focuses on targeted treatment based upon symptoms and signs present at onset to decrease disease burden and help restore baseline functioning as soon as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…However, there are a few compelling measurements that acutely reflect neuronal impairment from concussion/subconcussion, and thereby potentially hold the promise of gauging chronic neuronal damage. Easily administered visual and oculomotor function tests have recently shown such promise in sensitively detecting the effects of concussion [24,54,55]. One such test probes the ocular near point of convergence (NPC).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a few compelling measurements that acutely reflect neuronal impairment from concussion/subconcussion, and thereby potentially hold the promise of gauging chronic neuronal damage. Easily administered visual and oculomotor function tests have recently shown such promise in sensitively detecting the effects of concussion [24,54,55]. One such test probes the ocular near point of convergence (NPC).…”
Section: Introductionmentioning
confidence: 99%
“…The GST captures maximum head movement speeds in all three planes (horizontal yaw, vertical pitch, and roll plane) in degrees per second that an individual can perform while maintaining stable vision on a consistent sized computer-based target or optotype. 27,28 Optotype size was set to 0.2 logMAR above the established SVA value for the GST. The participant was instructed to slowly increase head velocity until the optotype appeared on the screen, with follow on-screen visual indicators to maintain consistent head displacement to the right and left, and to reach a trigger head velocity.…”
Section: Methodsmentioning
confidence: 99%
“…1,3,4 Visual and vestibular symptoms post-injury include blurry vision, diplopia, dizziness, and/or imbalance are reported in 50%-80% of athletes and are currently assessed as part of the comprehensive post-concussive evaluation. [5][6][7] Common acute post-injury assessments to include the Sport Concussion Assessment Tool, version 5, and King-Devick test provide information in regard to balance impairment and saccadic eye functioning, though do not capture function of the gaze stabilization system. [8][9][10][11] Assessment of vestibular ocular system dysfunction to include gaze stability is gaining recognition through both high-and low-technology assessments to include devices such as Eye Sync/SyncThink™ and the Vestibular Ocular Screening Tool (VOMs) which was designed for the non-vestibular practitioner to screen for vestibulo-ocular dysfunction following concussion.…”
Section: Introductionmentioning
confidence: 99%
“…Although most symptoms related to concussions resolve within 7 to 10 days, symptoms could last longer than a month significantly impacting academic performance. 59 Although concussion reportedly impacts the vestibular system [60][61][62][63][64] and vestibular rehabilitation is often prescribed for athletes with chronic concussion syndrome, 58,65 the studies that report vestibular system deficits in children with concussion do not directly measure the vestibular system using gold standard objective tests. Concussion diagnosis is, instead, based on symptom scales such as the vestibular oculomotor measurement scale.…”
Section: Concussionmentioning
confidence: 99%
“…Concussion diagnosis is, instead, based on symptom scales such as the vestibular oculomotor measurement scale. [60][61][62][63][64] Alshehri et al 66 showed no VOR deficit to the video head impulse test (vHIT) in 56 participants post-concussion, aged 10 to 20 years and determined that the vHIT test significantly increased symptoms of headache, dizziness, and nausea. Many of the intervention studies that reported the effectiveness of vestibular rehabilitation for patients with concussion are retrospective and not controlled.…”
Section: Concussionmentioning
confidence: 99%